Measurement of Anomalous Forces From a Cooper-Pair Current in High-Tc Superconductors With Nano-Newton Precision - Tajmar, M.; Neunzig, O.; Kößling, M. (Frontiers in Physics, 2022)
Does a supercurrent drag space-time or generate a gravitational field that can be measured in a laboratory environment? A number of theories suggest that space-time itself could be modeled as a superfluid, so a current of Cooper-pairs might couple to its surroundings differently compared to non-quantum matter. On the other hand, experiments appeared in the literature suggesting that a discharge through a high-Tc superconductor generates a force beam, which can be picked up by external sensors. We developed a unique facility to investigate if such a link exists with unprecedented accuracy. Instead of measuring with sensors far away from the superconductor, we built a very precise thrust balance that features a cryostat allowing to measure any anomalous force directly from the superconducting source. An onboard battery and a wireless-controllable power supply as well as strict coaxial current leads ensure that any magnetic interaction with its surroundings is below the measurement noise. Our tests were done for both BSCCO and YBCO superconductors with and without the presence of a magnetic field parallel to the current flow. No force was seen within our resolution of around 100 nN for currents up to 15 A. This puts strong limits on all proposed theories and experimental claims.